Courts in Latin America 2011
DOI: 10.1017/cbo9780511976520.004
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Deference in the Colombian Constitutional Court, 1992–2006

Abstract: Under what conditions are justices able to make decisions that are contrary to the executive's preferences in strong Latin American presidentialisms? To answer this question, I formulate a theory of interbranch relations, particularly of the interplay between courts and justices, on the one hand, and executives and legislatures on the other. The model of strategic prudence involves a game between two players-a court and a government-as well as a stage in which this game takes place, including the institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…In Colombia, "not only can any citizen present in front of a lower court but also, with very few formalities, any citizen can file a constitutional challenge to legislation (i.e., an abstract review case)". 117 The comparison between Brazil and Colombia presents relevant insights into how the dimension of authority and, specifically, standing to access the main courts in each system can make a large difference in the protection of social and individual rights.…”
Section: Resultsmentioning
confidence: 99%
“…In Colombia, "not only can any citizen present in front of a lower court but also, with very few formalities, any citizen can file a constitutional challenge to legislation (i.e., an abstract review case)". 117 The comparison between Brazil and Colombia presents relevant insights into how the dimension of authority and, specifically, standing to access the main courts in each system can make a large difference in the protection of social and individual rights.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps of greatest concern, scholars have suggested that in order to avoid conflict and non-compliance, judges often engage in politically deferential patterns of decision making, at least in particularly salient cases, which render the constraints they might place on governments practically non-binding (e.g., Bill Chávez and Weingast, 2011;Rodríguez-Raga, 2011;Carrubba, Gabel and Hankla, 2008;Chilton and Versteeg, 2018). Summarizing these challenges, USAID's Office of Democracy and Governance writes:…”
Section: Democracymentioning
confidence: 99%
“…134 While clearly subject to criticism, and more recently a serious scandal involving corruption, 135 the Court also has generally enjoyed a strong reputation for independence and the capacity to ensure compliance with its decisions. 136 In Indonesia, prior to a scandal involving corruption in 2011, the Constitutional Court generally was seen to have made a "significant contribution to Indonesia's transformation from a conflict-ridden, politically unstable country into a consolidating democracy" 137 and to have "performed with professionalism and integrity unmatched by Indonesia's other judicial institutions, perhaps even in Indonesian legal history." 138 In South Africa, both internal and external observers have celebrated the Constitutional Court's role in the transition to a multiparty democracy.…”
Section: Constitutional 'Design' Success and Drafter-judges As Lamentioning
confidence: 99%